On the gold-catalyzed intramolecular 7-exo-trig hydroamination of allenes - Pflästerer, Daniel; Dolbundalchok, Praphasiri; Rafique, Shahid; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2013)
Aniline derivatives with allene side tethers were tested as substrates for a gold-catalyzed 7-exo-trig hydroamination reaction. The nucleophilicity of the aniline derivatives plays an important role for the outcome of the reaction. While electron-deficient protecting groups at the nitrogen led to competing pathways like hydroarylation or an allene to diene isomerization, clean formation of the desired benzoxazepines was obtained with unprotected aniline derivatives.